Overuse injuries of the upper extremity in tennis players - Marx, R. G.; Sperling, J. W.; Cordasco, F. A. (Clinics in Sports Medicine, 2001)
Several overuse injuries can affect the upper extremity of tennis players. A thorough understanding of anatomy and knowledge of these common conditions and their treatment facilitates the management of these athletes.